The Influence of Social Relationships, Self-Esteem, and Empathy on Schadenfreude - Muhamad Khalid Akbar (‎‎‎TAZKIYA Journal of Psychology, 2022)
This study aims to examine the variables of social relationship, self-esteem, and empathy towards schadenfreude in Pagutan Villagers, Mataram, Indonesia. The researcher hypothesizes that there is a significant influence on the variables of social relations, self-esteem, and empathy towards schadenfreude in Pagutan Villagers. The population in this study is people who live in Pagutan Village and are aged between 22-55 years. The respondents in this study found 500 people. This sample was taken using a non-probability sampling technique, namely purporsive sampling. The researcher used the schadenfreude scale, the social relationship scale, the Rosenberg self-esteem scale, and the interpersonal reactivity index. Test the validity of the measuring instrument using confirmatory factor analysis (CFA) technique. Data analysis used multiple regression technique. The results of data analysis show that communication, selfesteem fantasy, and empathetic attention have a significant effect on schadenfreude. Meanwhile, social contact, perspective taking and its effect are not significant on schadenfreude. The results of the study also obtained an R-square result of .330 or 33%. That is, the proportion of variance from Schadenfreude explained by all independent variables is 33%, while the remaining 67% is influenced by other variables outside this study. The researcher hopes that the results of this study will be reviewed and developed again in further research by adding other variables.